Adjunct tele-yoga on clinical status at 14 days in hospitalized patients with mild and moderate COVID-19: A randomized control trial - Majumdar, Vijaya; Manjunath, N. K.; Nagarathna, Raghuram; Panigrahi, Suryanarayan; Kanchi, Muralidhar; Sahoo, Sarthak; Nagendra, Hongasandra R.; Giridharan, Adithi; Reddy, Mounika; Nayak, Rakshitha (Frontiers in Public Health, 2023)
Background The initial insights from the studies on COVID-19 had been disappointing, indicating the necessity of an aggravated search for alternative strategies. In this regard, the adjunct potential of yoga has been proposed for enhancing the effectiveness of the standard of care with respect to COVID-19 management. We tested whether a telemodel of yoga intervention could aid in better clinical management for hospitalized patients with mild-to-moderate COVID-19 when complemented with the standard of care. Methods This was a randomized controlled trial conducted at the Narayana Hrudyalaya, Bengaluru, India, on hospitalized patients with mild-to-moderate COVID-19 infection enrolled between 31 May and 22 July 2021. The patients (n = 225) were randomized in a 1:1 ratio [adjunct tele-yoga (n = 113) or standard of care]. The adjunct yoga group received intervention in tele-mode within 4-h post-randomization until 14 days along with the standard of care. The primary outcome was the clinical status on day 14 post-randomization, assessed with a seven-category ordinal scale. The secondary outcome set included scores on the COVID Outcomes Scale on day 7, follow-up for clinical status and all-cause mortality on day 28, post-randomization, duration of days at the hospital, 5th-day changes post-randomization for viral load expressed as cyclic threshold (Ct), and inflammatory markers and perceived stress scores on day 14. Results As compared with the standard of care alone, the proportional odds of having a higher score on the 7-point ordinal scale on day 14 were ~1.8 for the adjunct tele-yoga group (OR = 1.83, 95% CI, 1.11–3.03). On day 5, there were significant reductions in CRP (P = 0.001) and LDH levels (P = 0.029) in the adjunct yoga group compared to the standard of care alone. CRP reduction was also observed as a potential mediator for the yoga-induced improvement of clinical outcomes. The Kaplan–Meier estimate of all-cause mortality on day 28 was the adjusted hazard ratio (HR) of 0.26 (95% CI, 0.05–1.30). Conclusion The observed 1.8-fold improvement in the clinical status on day 14 of patients of COVID-19 with adjunct use of tele-yoga contests its use as a complementary treatment in hospital settings.